Gender Difference in Mathematics Anxiety across Different Ethnic Communities in Nepal - Paudel, Krishna Chandra (Education and Development, 2025)
Mathematics anxiety represents a significant psychological obstacle in educational contexts, particularly across diverse cultural sceneros. To investigate these gender disparities, this study examined mathematics anxiety across five ethnic/cultural groups in Nepal, applying a cross-sectional quantitative design to analyze the data from 625 participants (358 males, 267 females) representing five ethnic categories: Brahmins and Chhetris, Newar, Mongolians, Scheduled Caste, and Others. Independent samples t-tests and effect size calculations exhibited a statistically significant overall gender difference in mathematics anxiety (t = -3.4437, p < .001, d = 0.28), with females consistently reporting higher anxiety levels in four out of five ethnic groups. The Brahmins and Chhetris group demonstrated the most notable gender disparity (t = -4.4339, p < .001, d = 0.53). The findings highlight the complex interplay of gender and cultural factors in mathematical psychological experiences, suggesting the need for targeted educational interventions and culturally sensitive support strategies that address gender-based mathematical anxiety across those diverse ethnic contexts.